Composição zooplânctônica do rio Arienga (Município de Barcarena - PA), com ênfase nas espécies potencialmente bioindicadoras de qualidade de água - MARINHO FILHO, Adjalbas Nunes (2019)
In the region of Barcarena are installed some industries related to mining, especially: Imerys, Rio Capim Kaolin SA, ALBRAS SA, and SA ALUNORTE USIP, which are responsible for any accidents in the aquatic environment. In this context, the objective of this study was to characterize the composition of zooplankton Arienga River, a major tributary of the Para River, gathering information in a catalog on the bioindicators of water quality in the region, comparing them at different periods of precipitation rainfall for the North. Were collected in May (incidence rainfall) and August (lower incidence) in the year 2009. Were identified (eighteen) species of rotifers, cladocerans and tintinnids, and the presence of the orders Calanoida and Cyclopoida copepods of the class in the higher incidence of rainfall. For the less rainy period, were identified 21 (twenty one) taxon of rotifers, cladocerans and tintinnids and a few species belonging to the orders Calanoida and Cyclopoida copepods of the class. Were recorded the following taxon common to the two collection periods: Brachionus mirus, Filinia longiseta, Filinia terminalis, Keratella americana, Keratella cochlearis, Keratella lenzi, Trichocerca sp.1, Trichocerca sp.2 and Bdelloida between rotifers; Alonella daday, Bosmina hagmanni, Bosminopsis deitersi and Moina minuta among cladocerans. Besides the species of tintinnids and species belonging to orders calanoid and cyclopoid, with their immature stages. In both periods, there were no alterations in the group of rotifers, particularly in the posterior spine, the rotifer species Keratella cochlearis and Keratella americana, which occurred in the sampling stations. Similarly, Lecane lunaris occurred so infrequently and only in periods of low rainfall incidence for location. In the case of cladocerans, there were also no changes in shape (ciclomorfose/polymorphism), female sex bearing eggs (ephippia) or the presence of males in the environment that indicate significant changes in the aquatic environment, whether by natural causes, whether by anthropogenic causes. Finally, it suggests that, despite human activities developed in the resort, water quality can be considered, so far as suitable for development and reproduction of zooplankton species.